Mutual assistance between Federal Reserve Banks, 1913-1960 as prolegomena to the TARGET2 debate - Barry Eichengreen; Arnaud Mehl; Livia Chiţu; Gary Richardson (European Central Bank (ECB), 2014)
This paper reconstructs the forgotten history of mutual assistance among Reserve Banks in the early years of the Federal Reserve System. We use data on accommodation operations by the 12 Reserve Banks between 1913 and 1960 which enabled them to mutualise their gold reserves in emergency situations. Gold reserve sharing was especially important in response to liquidity crises and bank runs. Cooperation among reserve banks was essential for the cohesion and stability of the US monetary union. But fortunes could change quickly, with emergency recipients of gold turning into providers. Because regional imbalances did not grow endlessly, instead narrowing when region-specific liquidity shocks subsided, mutual assistance created only limited tensions. These findings speak to the current debate over TARGET2 balances in Europe.
Keywords: F30; N20; 330; Federal Reserve System; gold standard; liquidity and financial crises; monetary policy; risk sharing; TARGET2 balances; Clearing; Zentralbank; Teilstaat; Gold; Währungsreserven; Geldgeschichte; Währungsunion; USA; Eurozone